Joining TPP: Opportunities and challenges for Vietnam textile and garment industry - Nguyen, Thi Huong Trang (H. : ĐHQGHN, 2020)
With the overview of the textile and garment industry, this dissertation studies the situation of domestic production in order to give some recommendations to prepare for the joining in TTP play field.